Design and construction of mechanical onion slicing machine - Anthoni Lumbantobing; Saipul Bahri Daulay; Sulastri Panggabean (Universitas Sumatera Utara, 2014)
The slicing process is one of the postharvest processing. Onion slicing machine is used to support the increase of onion slicer product which is ready to be fried. This onion slicing machine uses electrical energy. This study was plan to build mechanical onion slicing machine. The study was conducted with literature study, experiment, observation and testing of the equpiment. The parameters measured were the effective capacity of the tool. The results showed that the effective capacity of the mechanical onion slicing machine was 76.1 kg/hour. Keywords: postharvest equipment, onion, slicer, effective capacity